Disrupting conventional conceptions of parental engagement: Insights from international schools. (January 2022) - McIntosh, Shona; Hayden, Mary
Recently, increases in numbers of international schools have been fuelled by a growth in numbers of aspirational families selecting them. The perception that international education affords children access to social advantages has been established in the school choice literature, but there has yet to be an examination of this trend in relation to parental engagement in international schools. Views of parents on this growing trend will be sought in a separate study, but in this paper we approach the problem through international school staff perceptions of issues relating to parents. These emerged during interviews with those responsible for implementing one part of the International Baccalaureate Diploma Programme: Creativity, Activity, Service. A communities of educational practice framework, adapted for parental engagement, indicated previously unidentified tensions in the international school/parent relationship. Conditions in international education markets create conditions that tip the balance of power, conventionally with the school, towards already-privileged international school parents, raising important questions about the relationship between international schools and social inequalities perpetuated by education.